Investigation of gelation mechanism and the effects of APS on AlN slurries with Isobam. Issue 14 (15th July 2021) - Ding, Ning; Zhi, Yi-Ru; Tian, Pei-Pei; Jiang, Hai; Lei, Wen; Fan, Gui-Fen; Wang, Xiao-Hong; Lu, Wen-Zhong
Abstract: A novel and simple gelling system based on a water-soluble copolymer of isobutylene and maleic anhydride (commercial name, Isobam) was adopted to manufacture various ceramics via spontaneous gelation. The gelation mechanism of AlN slurry was investigated using infrared spectroscopy. Results show that Isobam was hydrolyzed to produce the –COOH group, and the hydrogen bonding was formed between the –COOH and –CONH2 groups of Isobam during spontaneous gelation. Meanwhile, the gelling process of the Isobam system could be accelerated via enhancing hydrogen bonding through APS addition. With 1 wt% addition of APS, the gelation time reduced to 23 h, the viscosity of 50 vol% AlN slurry decreased to 0.21 Pa·s, and the flexural strength of green body improved by 48%. Therefore, the presence of hydrogen bonding in the Isobam gelation mechanism was confirmed, and it could be enhanced by introducing APS to accelerate gelation.